Police Culture, Procedural Justice, and Public Trust in Nigeria: A Community-Level Analysis - Ibrahim Adamu Bakori; Oluwasegun Agbailu Adejumo (African Journal of Law Political Research and Administration, 2026)
Police culture plays a critical role in shaping police–community relations, public trust, and the effectiveness of law enforcement institutions. In Nigeria, persistent allegations of corruption, brutality, and abuse of authority have continued to undermine the legitimacy of the Nigerian Police Force (NPF), despite successive reform initiatives. This study examines police culture and its contribution to mistrust, social incoherence, and citizen disempowerment within and between the NPF and the Saburi community in Abuja Municipal Area Council (AMAC), Federal Capital Territory (FCT), Abuja. Guided by procedural justice and police legitimacy theory, the study adopted a qualitative survey research design. Data were collected through structured, open-ended interviews with 60 purposively selected participants, comprising 30 police officers across different ranks and 30 community members representing diverse socio-economic backgrounds. The data were analyzed using thematic and content analysis, supported by word-frequency and word-cloud techniques with the aid of NVivo 12 and Microsoft Excel. The findings reveal that police culture within the NPF is characterized by entrenched informal practices, including leadership intoxication, abuse of authority, police brutality, selective enforcement, rent-seeking behaviour, and persistent SARS-related operational attitudes. These cultural practices were found to significantly undermine public trust, weaken social coherence, and systematically disempower economically vulnerable citizens by commodifying access to justice. The study further establishes that prevailing police culture hinders effective service delivery by discouraging crime reporting, reducing intelligence sharing, and weakening voluntary compliance with the law. Importantly, both police officers and community members acknowledged these cultural deficiencies, indicating that legitimacy deficits are institutionally recognized rather than solely externally perceived. The study contributes to policing scholarship by providing localized, community-level empirical evidence on the cultural drivers of police legitimacy deficits in Nigeria. It underscores the need for policing reforms that prioritize cultural transformation, ethical leadership, procedural justice, and meaningful community engagement to rebuild trust and improve service delivery.